Evaluation of the classification performance and cost-effectiveness of classification criteria in children with systemic lupus erythematosus - Rodríguez-Lozano, Ana Luisa; González-Garay, Alejandro Gabriel; Villasis-Keever, Miguel Ángel; Nájera-Velázquez, Ruth G.; Sáez-de-Ocariz, Marimar; Scheffler-Mendoza, Selma Cecilia; Rivas-Larrauri, Francisco Eduardo; Yamazaki-Nakashimada, Marco Antonio; García-De La Puente, Silvestre (Frontiers in Pediatrics, 2026)
BackgroundChildhood-onset systemic lupus erythematosus (cSLE) is a chronic autoimmune disease. In Latin America, the utility of the existing lupus classification criteria and their economic implications remain unexplored.ObjectiveTo evaluate and compare the utility and cost-effectiveness of the ACR-1997, SLICC-2012, and ACR/EULAR-2019 classification criteria in children with suspected cSLE.MethodsWe prospectively included subjects aged ≤17 who presented to the Immunology Department with suspected cSLE and consented to participate in the study. Exclusion criteria were pregnancy, tuberculosis, immunosuppressive therapy, malignancies, or insufficient data to apply the classification criteria. The ACR-1997, SLICC-2012, and ACR/EULAR-2019 lupus criteria were applied, followed by a referral for expert consensus diagnosis, which served as the standard of reference. We calculated the classification performance (how well a set of classification criteria assigns an individual to SLE or no-cSLE, measuring sensitivity, specificity, among others), direct healthcare costs for each classification, and developed a decision tree and quadrant graph for economic evaluation.ResultsNinety-six subjects (83% female) with a median age of 13.5 years were included in this study. The expert consensus diagnosis identified cSLE in 43 subjects; ACR and ACR/EULAR each identified 42 cases, while SLICC identified 56. The sensitivity was 98% for SLICC-2012, 84% for ACR-1997, and ACR/EULAR-2019, p = 0.000). The cost per subject per classification was USD 287.62 for SLICC-2012, USD 174.97 for ACR-1997, and USD 310.36 for ACR/EULAR-2019 (p = 0.596).ConclusionThe SLICC-2012 criteria were the most sensitive for the classification of SLE, but not the most cost-effective. ACR-1997 remains the most cost-effective tool in specialized settings; however, the higher sensitivity of SLICC-2012 supports its use to improve early referral.